Dasatinib-Induced Hypopigmentation in Pediatric Patient with Chronic Myeloid Leukemia: A Case Report and Review of the Literature - Bader Alharbi; Samer Alamri; Ahmed Mahdi; Siham Marghalani (Case Reports in Dermatological Medicine)
Dasatinib is an oral second-generation multitarget tyrosine-kinase inhibitor (TKI) that is efficacious in treating imatinib-resistant chronic myeloid leukemia (CML) or intolerant cases. Noncutaneous adverse effects with dasatinib are well known in the literature, most commonly cytopenias and fluid retention, while pigmentary abnormalities have rarely been reported. We report the case of a 12-year-old male known case of CML, who presented to dermatology clinic approximately 2 years after initiating dasatinib treatment, with new-onset hypopigmentation of his upper limb, upper chest, and both knees of six months’ duration.